Central Corneal Thickness Changes after Phacoemulsification - Wajiha Koomal, Khabir Ahmad, Tanveer Anjum Chaudhry, Muhammad Hamza (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine when the mean central corneal thickness (CCT) returns to normal values after uneventful phacoemulsification. Material and Methods: This was a prospective case series. The study was carried out at the Section of Ophthalmology, Department of Surgery, Aga Khan University Hospital, Karachi. Eyes scheduled to undergo phacoemulsification during December 2011 – March 2012 were eligible to be included. Eyes with corneal degenerations, dystrophies or high pre-op astigmatism were excluded. A structured proforma was used to collect data on sociodemographics, comorbids, visual acuity, and CCT before surgery and 1 day, 1 week and 1 month after surgery. Changes in the mean CCT over time were measured using repeated measures Analysis of Variance (ANOVA) was done. Results: Eighty one eyes were included in the study. The mean (±SD) age of the participants was 58.30 (± 10.04) years. The majority of them (58.0%) were women. Sixty two (76.5%) eyes completed the last follow-up and were included in the final analysis. The mean CCT was 542.81 ± 34.85 mm before surgery which markedly increased to 595.27 ± 43.78 mm 24 hours after surgery, but decreased to 565.82 ± 38.30 at one week, and returned to normal baseline values (544.42 ± 28.95) in almost all operated eyes in 1 month time. There was no statistically significant difference in the mean CCT before surgery and at 1 month (p=0.685). Conclusion: The mean CCT substantially increasing after post-operative uneventful cataract surgery but returns to normal baseline values in almost all operated eyes in 1 month time. IOP measured during this period may be falsely higher than the true values due to increased CCT. Key words: central corneal thickness, phacoemulsification, cataract surgery